Protocol for a scoping review of time to treatment in adults with newly diagnosed multiple myeloma - Matthew R. LeBlanc; Allison O. Taylor; Osborn Owusu Ansah; Jamie Conklin (PLoS ONE, 2025)
Background Delays in cancer treatment can result in tumor growth, increased clonal heterogeneity, upstaging, increased symptoms, organ damage, increased psychological distress, and worse clinical outcomes. Evidence supported guidelines for treatment timeliness exist in many cancers, but not for multiple myeloma (MM) though there is reason to believe delays in treatment would be detrimental. Aims This scoping review aims to explore what is known about the impacts of the time from diagnosis to treatment among patients with MM. Methods Our review will be guided by the Joanna Briggs Institute scoping review methodology. Our search strategy was developed to identify sources published in or after the year 2000 related to time to treatment for adults with newly diagnosed multiple myeloma in PubMed, CINAHL, Scopus and Embase. Sources will be screened by two independent reviewers after exclusion/inclusion criteria are pilot tested and refined. A data extraction form was developed and will be refined by the study team for use during the scoping review. Discussion This review will summarize the landscape of research related to time to treatment among newly diagnosed adults with multiple myeloma. Raising awareness of the available evidence on this topic, within the MM clinical and research community, will guide future research to address identified knowledge gaps. Registration This protocol was registered with Open Science Framework (OSF) on the 25th of March, 2025 and can be found at osf.io/sydqw.